New Synthesis of a Dibenzoperylene Motif Featuring a Doubly Boron–Nitrogen-Doped Bay Region - Fingerle, Michael; Stocker, Simon; Bettinger, Holger F. (Synthesis, 2019)
A dibenzoperylene motif featuring a doubly boron–nitrogen-doped bay region is accessible from an aniline derivative in six steps in good overall yield. Two n-butyl groups provide the BN-doped polycyclic aromatic hydrocarbon with sufficient solubility in common organic solvents. The synthesis sequence allows installation of a second boron atom next to a weakly nucleophilic nitrogen by using a protected boron species. The title compound shows blue fluorescence, an extremely high fluorescence quantum yield, and an interesting doped bay region.
Keywords: boron; chromophores; nitrogen; azaborinines; polycycles